Salinity Duration Differently Modulates Physiological Parameters and Metabolites Profile in Roots of Two Contrasting Barley Genotypes - Dell’Aversana, Emilia (Plants (Basel), 2021)
Hordeum maritimum With. is a wild salt tolerant cereal present in the saline depressions of the Eastern Tunisia, where it significantly contributes to the annual biomass production. In a previous study on shoot tissues it was shown that this species withstands with high salinity at the seedling stage restricting the sodium entry into shoot and modulating over time the leaf synthesis of organic osmolytes for osmotic adjustment. However, the tolerance strategy mechanisms of this plant at root level have not yet been investigated. The current research aimed at elucidating the morphological, physiological and biochemical changes occurring at root level in H. maritimum and in the salt sensitive cultivar Hordeum vulgare L. cv. Lamsi during five-weeks extended salinity (200 mM NaCl), salt removal after two weeks of salinity and non-salt control. H. maritimum since the first phases of salinity was able to compartmentalize higher amounts of sodium in the roots compared to the other cultivar, avoiding transferring it to shoot and impairing photosynthetic metabolism. This allowed the roots of wild plants to receive recent photosynthates from leaves, gaining from them energy and carbon skeletons to compartmentalize toxic ions in the vacuoles, synthesize and accumulate organic osmolytes, control ion and water homeostasis and re-establish the ability of root to grow. H. vulgare was also able to accumulate compatible osmolytes but only in the first weeks of salinity, while soon after the roots stopped up taking potassium and growing. In the last week of salinity stress, the wild species further increased the root to shoot ratio to enhance the root retention of toxic ions and consequently delaying the damages both to shoot and root. This delay of few weeks in showing the symptoms of stress may be pivotal for enabling the survival of the wild species when soil salinity is transient and not permanent.